The Impact of Change in Trade Regime on Lithuanian Textile and Apparel Industry - Miškinis, Algirdas; Kasnauskienė, Gindra; Vaiginienė, Erika (Ekonomika, 2006)
Two recent events had a tangible impact on Lithuanian textile and apparel industry. First of them was Lithuanian EU membership and entrance to the single market, the second one being the final abolition of quantitative restrictions in the sector from the beginning of 2005. The outcomes of the first event are less significant as tariffs in trade with the EU were removed in line with the bilateral free trade agreement concluded long before Lithuanian EU membership. The EU membership resulted in more changes in the trade regime with the third countries. Before membership Lithuania applied only a few restrictions while the EU common trade policy envisaged the application of both quantitative restrictions and tariffs. A more tangible impact on Lithuanian textile and apparel industry had the abolition of quotas which affected to a less extent Lithuanian market and 10 a larger extent the EU market where 90% of Lithuanian sector exports are supplied.The purpose of the article was to explore the situation in the sector after these two major events, to identify the problems and 10 disclose the prospects for the development of the sector in the light of new challenges and to look for the possibilities to increase and diversify the sector’s exports.Lithuania is one of the EU countries most specialized in the textile and apparel sector. In 2004, the sector produced 13.8% of manufacturing value added and exported 11.6% of the total Lithuanian exports. 63% of the sector’s exports are apparel exports. 80% of the sector’s output is assigned for export.The abolition of quantitative restrictions and application of low tariffs for textile and apparel products for imports from third countries have caused severe problems in competition with imports from China and other countries of cheap labour. The textile subsector was growing steadily until 2003, however, since January 2005, when quotas were abolished, textile outputs are shrinking. This is a result of the booming import of apparel from China and other developing countries. These imports reduced the production of these products in the EU and resulted in a reduction of fabric imports from Lithuania. The apparel subsector reached its peak in January 2004. Since then this subsector. in which more than half volume comprise items for which quotas were removed. faces a very severe competition from China, India, Turkey and other countries. Statistics revealed that when production in the sector is decreasing the consumption is increasing. In 2005. in comparison with 2000, sales of textile, apparel and leather products increased by 174.7% (10.3% in the EU).Evaluating the current situation in the sector, authors draw attention to the Following weaknesses of the sector: prevalence of low value added activities, especially in the apparel subsector; diminishing of competitive advantages as a result of labour becoming more expensive and a standstill in productivity, inadequate investments in new technologies, shortage of management and marketing competence, lack of cooperation between textile and apparel companies. missing government support to the sector.Authors believe that the sector has also a number of strengths which allow it to remain competitive at least in the near future. Among them, the modernization of technologies in most advanced companies. the geographical proximity of European markets, a good labour and product quality should be mentioned.Authors believe that new opportunities for the sector would be opened by innovations in new technologies. materials and products, an enhancement in labour skills and competencies. a faster reaction to changes in needs and demand, a shift from mass production of simple products to a larger variety and higher value added products with big design content, larger application of local designers’ skills, development of technical textile and non-woven fabrics, a transfer of labourintensive cycles of production to countries with cheaper labour like Ukraine and Belarus, better cooperation between producers. wholesalers and retailers.Lithuanian textile and apparel industry should penetrate new markets. For the moment, 90% of the sector products are exported to the EU market. Such dependence on the market makes Lithuanian export very vulnerable, and therefore there is a need t9 diversify markets and to look for new export destinations. Success in these markets depends nol only on company actions but also on the EU attempts to increase access to these markets. Most of these markets are still greatly protective. In bilateral and multilateral negotiations the European Commission should seek to reduce high tariffs in some developing countries and should require removal of all non-tariff barriers.